Understanding the Use of Adjective Order for Senior High School 21 Makassar - Abdollah Abdollah; Muhammad Yunus; Effander Elivan (Fakultas Sastra - Universitas Muslim Indonesia, 2018)
The present study is about the ordering adjective in adjective order. In this study the writer explores the students’ understanding and the student errors in the adjective order term. The writer employed pre-experimental method with one group pre-test and post-test design. The sample consisted of 40 students taken from the second class of SMA Negeri 21 Makassar, academic 2014/2015. The data were collected by giving the student test. The data collected were analyzed by using scoring classification, mean score and percentage. To find out whether fighting question method can improve student understanding in ordering adjective orders and what is the most student errors in term adjective order. The result of the data analysis showed that there was a significant difference between pre-test and post-test. The value of mean of mean score post-test (69) is greater than the pre-test (43.25) and the most students errors in adjective order term is the position of an adjective ”Shape”.